A better way to manage severe dentofacial-disproportions in conjunction with end stage tmj-arthropathy. Issue 1 (January 2022) - Halsnad, Moorthy
Abstract : Introduction : The management of younger patient groups with severe dentofacial disproportions that are caused primarily from temporomandibular disease process are often considered challenging clinical scenarios. Most patients routinely undergo several surgical procedures often not reaching satisfactory functional and aesthetic outcomes. The most common concerns that discourage such individuals seeking surgery are; a) complications of surgery b) facial weaknesses c) scar d) multiple surgeries e) sub optimal outcomes of joint function & aesthetics. The purpose of this presentation is to demonstrate the author's technical modifications in comprehensive management of dentofacial-disproportions secondary to tmj arthropathy with a single stage simultaneous tmj replacements along with orthognathic surgery. Methods : The presentation will review case series of tmj arthropathy cases that presented with severe forms of dentofacial disproportions. This will include assessments, investigation findings, surgical preparations including 3 dimensional planning for patient specific implants for tmj prosthesis and surgical technique. Results : All surgical cases are operated and managed by single surgeon. The planning and execution of interventions have achieved a high rate of satisfaction with very minimal morbidity. The modifications of surgical techniques have significantly benefited each patients to reach the main objective of fulfilling patient expectations with one definitive surgery. Conclusions : The presentation will conclude that the author's technical modifications in a single stage interventions have achieved significant improvements in the final outcomes of patients with very minimal morbidity. The presentation will confirm author's concepts to be a better way to manage severe dentofacial-disproportions in conjunction with end stage tmj-arthropathy.